SIMULASI ANALISIS DAMPAK LALU LINTAS MENGGUNAKAN PTV VISTRO (STUDI KASUS : KOMPLEK RUKO BERJAYA BATAM) - Rifai, Arif; Sulistyono, Sonya; Soetjipto, Jojok Widodo (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Traffic Impact Analysis (TIA) is study on the impact of development on the surrounding transportation network. Complex Ruko Berjaya is a commercial and residential complex that will be built on the city of Batam.This area has been done but the traffic impact analysis using the manual calculation method MKJI . For traffic impact analysis was performed on the complex of the RukoBerjaayaBatam use PTV Vistro . Analysis on PTV Vistro will be compared with MKJI method that performed on the input volume adjustment. There are differences in the determination of the saturation flow and the capacity of the two methods, which produce the PTV Vistro capacity greater than MKJI. Output performance PTV Vistro  results show a lower value than the calculation MKJI.